Modernity and Sustainable Development: Reframing the Diagnosis and Prognosis: Exploring the Link Between Modernity, Capitalism, and Sustainable Development (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Modernity is the distinct, multidimensional and unique form of social life and got identified with industrialism, Science and Technology and Development in general and Capitalism in particular. Being a visionary development paradigm and as a guiding principle, Sustainable Development calls for a convergence between the three pillars of economic development, social equity, and environmental protection. But the concept remains elusive and implementation has proven difficult and has often been compartmentalized as an environmental issue. This paper tries to investigate the relevance of Sustainable development and role of capitalism in the economic development environmental and environmental degradation and critiques of capitalism and prescribing some policies for the promotion of sustainable development.